A simple model for high rotational excitations of molecules in a superfluid - Cherepanov, Igor N.; Bighin, Giacomo; Schouder, Constant A.; Chatterley, Adam S.; Stapelfeldt, Henrik; Lemeshko, Mikhail (Arxiv, 2022)
We present a simple quantum mechanical model describing excited rotational states of molecules in superfluid helium nanodroplets, as recently studied in non-adiabatic molecular alignment experiments [Cherepanov et al., Phys. Rev. A 104, L061303 (2021)]. We show that a linear molecule immersed in a superfluid can be seen as an effective symmetric top, similar to the rotational structure of radicals, such as OH or NO, but with the angular momentum of the superfluid playing the role of the electronic angular momentum in free molecules. The model allows to evaluate the effective rotational and centrifugal distortion constants for a broad range of species and to explain the crossover between light and heavy molecules in superfluid $^4$He in terms of the many-body wavefunction structure. Most important, the simple theory allows to answer the question as to what happens when the rotational angular momentum of the molecule increases beyond the lowest excited states accessible by infrared spectroscopy. Some of the above mentioned insights can be acquired by analyzing a simple 2x2 matrix.